MORAL CULTURE AS THE BASIS OF PROFESSIONAL VALUES OF THE FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2008)
The article reveals the essence of concept “morality culture”, defines its proofs and levels forming of the morality culture of students. The article investigates the connection with professional value of future teachers.